2020
DOI: 10.1177/0960327120947793
|View full text |Cite
|
Sign up to set email alerts
|

Histoprotective effect of rutin against cisplatin-induced toxicities in tumor-bearing mice: Rutin lessens cisplatin-induced toxicities

Abstract: Cisplatin is an effective anticancer drug used against a variety of cancers. The full therapeutic potential of cisplatin is often hampered due to concurrent development of various side effects in the hosts. Rutin, a naturally occurring bioflavonoid shows several pharmacological activities. It has been earlier reported by us that rutin and cisplatin in combination show better antitumor activity against murine ascites Dalton’s lymphoma. As cisplatin is given to cancer-bearing hosts only, the present study was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…investigated the protective effect of rutin on cisplatin‐induced toxicities in tumor‐bearing mice. The results showed that this antioxidant was able to reduce toxicities by reducing free radicals [18] . Rutin appears to be an effective antioxidant in the treatment of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…investigated the protective effect of rutin on cisplatin‐induced toxicities in tumor‐bearing mice. The results showed that this antioxidant was able to reduce toxicities by reducing free radicals [18] . Rutin appears to be an effective antioxidant in the treatment of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 94%
“…The results showed that this antioxidant was able to reduce toxicities by reducing free radicals. [18] Rutin appears to be an effective antioxidant in the treatment of hepatotoxicity. In our study, paraquat-induced hepatotoxicity decreased liver catalase and superoxide dismutase activity (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐inflammatory and anti‐tumour activities of ursurane triterpenes such as asiatic acid and TEOA have been widely recognised 36–38 . Rutin and catechins are flavonoids and are widely used in cancer research 39,40 . Coumarins, including aesculin, esculetin, and 5,7‐dihydroxytryptophenone, also have anti‐inflammatory and anti‐tumour effects 41–43 .…”
Section: Resultsmentioning
confidence: 99%
“…[36][37][38] Rutin and catechins are flavonoids and are widely used in cancer research. 39,40 Coumarins, including aesculin, esculetin, and 5,7-dihydroxytryptophenone, also have antiinflammatory and anti-tumour effects. [41][42][43] Protocatechuic, ferulic, and syringic acids are phenolic acids with anti-inflammatory and antioxidant activities.…”
Section: Network Pharmacology Analysismentioning
confidence: 99%
“…These findings also supported by the results of cisplatin group but the intensity of results were directed toward the cerium oxide nanoparticles. These results were augmented by [27 ] although these authors showed increase in GPx antioxidant Although the cisplatin is used as chemotherapy in the treatment of cancer that had excellent penetration power [28 ] but it had numerous side effects [ 29 ] that lead the pharmacist to search for another substitutes that had low tissue toxicity [ 30 ].The cisplatin accumulation encourages cellular apoptosis and cytotoxicity [31,32 ] In contrast to our work that cisplatin decreased MDA and increased SOD and showed improvements in histopathological alteration in the tumour skeletal muscle [33 ]showed increased MDA and decreased SOD and Gpx. Cisplatin also accelerated the cells to undergoes apoptotic pathway [34 ] Owing to the industry's extensive usage of cerium oxide nanoparticles [Ceo2 NPs; nanoceria (NC)] and their employment in biology and medicine, researchers have lately been interested in examining their antioxidant qualities.…”
Section: Discussionmentioning
confidence: 99%